Comparative Analysis On The Evolution Of Legendary and Historical Heroes In Western and Eastern Literature - Nasrullayeva, Umida (Jurnal Teknologi Pendidikan, 2024)
This article explores the evolution of legendary and historical heroes in Western and Eastern literature, analyzing their characteristics, cultural significance, and transformations across time. Heroes, whether mythical or historical, reflect societal values, struggles, and aspirations. While Western heroes often embody individualism, self-sacrifice, and triumph over adversity, Eastern heroes tend to emphasize collective responsibility, honor, and spiritual growth. By comparing iconic figures such as King Arthur and Hercules from Western traditions with Eastern counterparts Maanguberdi and Timur, this study highlights similarities and divergences in their representation, evolution, and cultural impact.